Study, dimensioning and realization of a fire fighting - SEMASSOU, GUY CLARENCE; AHOUANSOU, ROGER H. (My University, 2022)
An analysis of the SCB-Lafarge Onigbolo fire network shows that in addition to its advanced age, it presents a number of irregularities. Indeed, this network delivers a low pressure to the water points. For example, the water cannon receives a pressure of 2.5 bars when it requires a pressure of 3.5 bars. This network also has an insufficient number of water points around the fuel piles. For example, there is only one fire hydrant around the petcoke hall containing 30,000 tons of fuel. Moreover, in case of a power cut, this network does not work because it is supplied by electric pumps. After the study of the various problems, it was decided to build a new fire network. This network is dedicated only to fire fighting and is supplied by a diesel pump. It is made of high-density polyethylene and stainless-steel pipes. These pipes are of nominal diameter constituting the secondary and main sections respectively. The number of fire hydrants has been doubled around the fuel piles and the water tank has been sized accordingly. This new network is capable of supplying two fire hydrants simultaneously with the right pressure and flow rate, in addition to a reinforced fire hydrant. The cost of the network is eighty million two hundred and seventy-seven thousand four hundred and sixty-four point five (80 277 464.5) CFA francs.
Keywords: Fire-fighting system; Low pressure; Diesel pump; Fire hydrant